The mutagenic and antimutagenic activity of Sutherlandia frutescens extracts and marker compounds - Siyabulela S. B. N. Ntuli; Wentzel C. A. Gelderblom; David R. Katerere (BMC, 2018)
Abstract Background Sutherlandia frutescens (L.) R. Br is endemic to Southern Africa where it has been traditionally used for cancer and diabetes. In recent times it has been marketed for its reputed (but not proven) anticancer, antidiabetic and anti-HIV properties. Little is known about the mutagenic and antimutagenic potential of extracts and common marker compounds of Sutherlandia frutescens. Therefore this study aimed to investigate the putative efficacy and possible long-term adverse effects of using this herb. Methods Ethylacetate (EA) and 50% Methanol (MeOH) extracts were screened for mutagenic and antimutagenic activity using the Ames assay utilising TA97a, TA98, TA100 and TA102 in the presence and absence of metabolic activation. Four compounds, L-arginine, L-canavanine, GABA and D-pinitol known to occur in sutherlandia were also included. The total polyphenolic content of the both extracts was determined using the Folin-Ciocalteau method and FRAP and ABTS were used to determine the anti-oxidant potential of the extracts. Results The extracts and the standards did not show any cytotoxicity except in TA97a. The EA extract exhibited antimutagenicity against all the bacterial strains at all concentrations tested. The MeOH extract showed both pro-mutagenic and antimutagenic activities with 2-acetamidofluorene and aflatoxin B1 in the presence of metabolic activation of TA98 and TA100, respectively. All compounds, except L-canavanine exhibited antimutagenic activity against all strains. L-canavanine, on the other hand showed co-mutagenicity with 9-aminoacridine on TA97a, at all test concentrations. The extracts and pure compounds exhibited their antimutagenic activity in a dose response manner. L-arginine and GABA showed an some antimutagenic response. EA extract had three times the total phenolic content (12.56 μg GE / mg) observed in the MeOH extract. There was correlation between total phenolic content, antioxidant potential and antimutagenicity. Conclusion Both extracts exhibited a protective effect, with the EA extract exhibiting greater potency. L-canavanine acted as a co-mutagen in a dose response manner without metabolic activation. It is suggested that the EA extract be priotized for future development work as it showed a better risk profile and activity.